Adam’s Root (Thamus Communis) - Forgotten Medicinal Plant in Georgia - Nikandish, Mehrasa; Qurashvili, Nino; Chikava, Medea (Caucasus Journal of Health Sciences and Public Health, 2020)
Aim.The aim of our studies was to collect and analyze Georgian literature data on Thamus communis that has been used in Georgian folk medicine for centuries but has eventually been forgotten. Materials and methods. The material of the article was Georgian literature data which were processed by methods of generalization and systematization. Results. Tamus communis mainly grows in mountain beech, oak and chestnut forests in almost all regions of Georgia. Botanical dictionary by A. Makashvili mentions this plant as Mikhelta. Having studied old medical handbooks, we stated that in the medieval time, Thamus communis was known as Kustiandwas used as a single herb as well as in combination with other medicinal plants mainly in the form of water and alcoholic extracts and tinctures. Iadigar Daudi, the 17th century Georgian medical handbook by David Bagrationi,describes Kusti as incomparable remedy for epileptic seizures, in acyesis treatment, for avoiding nightmares, resolving digestion problems, and relieving joint pain, swelling, and inflammation. According to the Book of Medical Treatment by Zaza Panaskerteli-Tsitsishvili,15thcentury, Kusti was a remedy for relieving acute back pains, resolving digestion problems, treating bladder inflammation, gallbladder diseases. The most interesting fact is that this plant was successfully used in the treatment of hemangioma and liver tumors. Kananeli in his Incomparable Karabadini (medical handbook),11th century, provides the well tested remedy for removing pockmarks and other face spots. The main ingredient of his remedywas Kusti roots. Since the 17th century, Thamus communis disappeared from the medical handbooks. Only in late 1930s, Megrelishvili N., a Georgian physician, dedicated his doctoral thesis to Thamus communis. He ascribed the plant analgesic properties to calcium oxalate isolated from the roots of Thamus communis and stated that the plant heals rheumatic diseases by local mechanical irritation.